Uniões estáveis plúrimas e o reconhecimento do direito sucessório - Cintra, Najla Lopes (2016)
This study aims to analyze the relationships that occur simultaneously among three or more people, with the consent of all of those involved and in a public way. The work's goal is to demonstrate that solutions brought by the lawmakers are not always capable to reach a group's aspiration, and these groups are compelled to search for the Judiciary System to see their rights ensured. However, many jurists' conservative thoughts prevent everyday's situations to be acknowledged, putting the cold letter of law above the individual's autonomy and human dignity. It will study monogamy and its usage as a principle or as an orientation rule. Family pillar principles will be brought up, as well as the comparison between the duties of fidelity and loyalty related to marriage and civil union. The analysis of possible effects resulting from these relationships will observe the good faith's existence and finally it will discuss succession matters concerning these arrangements